Bringing anime to academic libraries: a recommended core collection. Issue 2 (1st April 2014) - Pope Robbins, Laura
Abstract : Purpose: – This paper aims to provide reasons for developing an anime collection within academic libraries as well as providing guidance in starting such a collection. Design/methodology/approach: – This paper is based upon research of literature and anime-related websites, as well as familiarity gained through viewing anime. Findings: – Anime is a medium that can be used to explore all genres, as well as universal themes, and provide a glimpse of Japanese life. The study of film has been accepted for decades and the study of animation has grown from that but has been restricted to primarily American animation. Anime is animation specific to Japan which can inspire students and faculty to explore another culture. Libraries should provide classic anime that can support cross-cultural and interdisciplinary studies. By creating an anime collection, a library will provide their community with engaging materials that can be used for enjoyment as well as study. A list of core titles is included. Originality/value: – This paper reflects recent trends toward increased interest in Japanese popular culture, specifically anime, and offers academic libraries a rationale for including such materials within their collection to connect with their students and faculty. There are no articles on the topic of collecting anime in academic libraries.